MATUR: Web-Based Platform Innovation to Facilitate Final Assignment Management in Higher Education - Rozi, Fathor; Ni'am, Muhammad Durrin; R, Abu Hasan Agus; Adeoye, Moses Adeleke; Bolaji, Hameed Olalekan (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2025)
This study aims to develop and implement a web-based platform,